2021
DOI: 10.3390/su13105473
|View full text |Cite
|
Sign up to set email alerts
|

The Role of UNESCO Cultural Heritage and Cultural Sector in Tourism Development: The Case of EU Countries

Abstract: Culture and tourism have always been related, but with blurred interpretations of the empirical relationship between those phenomena. This paper estimates the impact of different cultural indicators on tourism development in 27 EU member states for the period 2008–2018, by using dynamic panel data. The results indicate that the number of UNESCO Heritage Sites do not have a significant influence on the number of tourism overnights, whereas there are significant positive effects on international tourism receipts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…Similar phenomena apply to many different UBH sites of similar importance-it is a common process assessed as a positive change, which is discussed in many publications. The sites themselves are perceived as more attractive than before being listed [108,109]. Visits to salt mines listed by UNESCO influence direct the perception of tourists to their main values, namely their features and history.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar phenomena apply to many different UBH sites of similar importance-it is a common process assessed as a positive change, which is discussed in many publications. The sites themselves are perceived as more attractive than before being listed [108,109]. Visits to salt mines listed by UNESCO influence direct the perception of tourists to their main values, namely their features and history.…”
Section: Discussionmentioning
confidence: 99%
“…Visits to salt mines listed by UNESCO influence direct the perception of tourists to their main values, namely their features and history. The results of studies addressing this approach have often been discussed based on experiences from different European countries with a number of sites on the UNESCO list [109][110][111][112][113]. However, to increase the understanding of the impact on the local community is a relevant issue to make both cities and the salt mines more safe, inclusive, resilient, and sustainable.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated the cultural heritage potential of Nitra to be sufficient for the city to become an important cultural tourism hub in the region. Research by Škrabić Perić [58] showed that the number of UNESCO heritage sites does not significantly affect the growth of accommodation facilities' capacity but significantly contributes to the size of the tourism job market and income from international tourism. Moreover, other characteristics of the culture sector that were investigated, i.e., government spendings on culture and employment in culture, turned out to have a significant positive influence on the growth of cultural tourism.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, it seems that living near tangible or intangible heritage, thus the value associated to heritage existence, could indirectly contribute to quality of life by means of improving material conditions or enhancing mutual understanding, for instance through tourism [8]. Alternatively, it could be that the existence of heritage has both positive and negative effects, for example when benefits such as the creation of economic activity [41] or the possibility of enjoying a historic city or landscape cancel out with the inconveniences generated by cultural tourism due to overcrowding or gentrification, as in [26,27].…”
Section: Discussionmentioning
confidence: 99%